Delayed primary repair for isolated esophageal atresia: Preliminary reports from Marmara group [İzole özofagus atrezisinde geciktirilmiş primer onarim: Ön sonuçlarimiz] - (:unkn) unknown (My University, 2000)
Repair of isolated esophageal atresia (EA) is still a challenging problem. We have reviewed our experience with delayed primary anastomosis by Livaditis myotomy (LM) to assess the efficacy, practicability and safety of this approach. From 1989 to 2000, five cases of long-gap isolated EA were admitted. Among these patients, four underwent DPR and remaining one (the first patient of this series) was lost preoperatively due to aspiration. Postoperative complications, feeding pattern and weight gain were assessed. Primary anastomosis was possible in all patients during secondary operation. Their ages at operation were ranged between 2.5 to 5 months, and the gap was measured 3.5 to 4.5 vertebral bodies in length. A proximal fistula was demonstrated during surgery in one of the cases. LM in various number (1 to 3) was required to achieve a successfull primary anastomosis in all patients: A proximal fistula was recognized during the operation in one of the patient. All patients had some early postoperative complications (stricture in all and leak in one). Anastomotic leak healed spontaneously. During the 2 months to 4.5 (mean 2.4) years of follow-up period, feeding quality, esophageal peristalsis and motility of the patients were comparable with those who had esophageal repair for EA and distal fistula. On the basis of our experience, DPR remains our treatment of choice for isolated atresia.
Keywords: Circular myotomy; Delayed primary repair; Esophageal atresia